Palladium and copper catalyzed Sonogashira cross coupling has been an excellent methodology for C-C bond formation for 17 years: a review - Kanwal, Iram; Mujahid, Aqsa; Rasool, Nasir; Rizwan, Komal; Malik, Ayesha; Ahmad, Gulraiz; Shah, Syed Adnan Ali; Rashid, Umer; Mad Nasir, Nadiah (MDPI, 2020)
Sonogashira coupling involves coupling of vinyl/aryl halides with terminal acetylenes catalyzed by transition metals, especially palladium and copper. This is a well known reaction in organic synthesis and plays a role in sp2-sp C-C bond formations. This cross coupling was used in synthesis of natural products, biologically active molecules, heterocycles, dendrimers, conjugated polymers and organic complexes. This review paper focuses on developments in the palladium and copper catalyzed Sonogashira cross coupling achieved in recent years concerning substrates, different catalyst systems and reaction conditions.